Chapter Presentazione - Una costellazione di saperi per l'autogoverno e la cura dei luoghi come beni comuni - Magnaghi, Alberto (Territori, 2023)
To become more than a mere intellectual construction, eco-territorialism requires that each science involved looks critically at its own disciplinary boundaries and explores border zones rich of fruitful contaminations, playing an aware and open part in a sort of choral music score. In this brief presentation, the editors describe the argumentative structure of the book and point out key concepts necessary in order to build a real alternative to ecological crisis and deterritorialisation.